Bilateral lung disease, extensive and diffuse. Diagnosis of pulmonary alveolar proteinosis by bronchoscopic cryobiopsy. (2017) - Gando, Sebastián; Duré, Roberto; Violi, Damián; Vazquez, Bibiana; Labarca, Gonzalo; Fernandez-Bussy, Sebastián
Abstract: Pulmonary alveolar proteinosis (PAP) is a rare disease characterized by the intra-alveolar accumulation of a proteinaceous phospholipid-laden material called surfactant. Clinically, this disease should be suspected with respiratory failure in association with a crazy paving pattern on high-resolution chest computed tomography. We report a 24-year-old gentleman who was referred to us for a history of respiratory failure, treatment with invasive ventilation and tracheostomy. His blood exams and biochemistry were normal. His infectious and rheumatological panel was negative for a secondary disease. A flexible bronchoscopy with a transbronchial biopsy through a CryoProbe was performed. An anatomopathological analysis was periodic acid-Schiff positive for PAP. A CryoProbe is a recently developed diagnostic tool that improves the diagnostic yield in diffuse lung diseases compared to bronchoscopy with transbronchial biopsy. This method should be considered for patients with diffuse lung disease and PAP.